2021
DOI: 10.3389/fimmu.2021.637753
|View full text |Cite
|
Sign up to set email alerts
|

Lipoxin A4 Restores Septic Renal Function via Blocking Crosstalk Between Inflammation and Premature Senescence

Abstract: Acute kidney injury (AKI) occurs in half of patients with septic shock, resulting in unacceptably high mortality. However, effective preventive treatments are still lacking. We hypothesized that pretreatment with lipoxin A4 (LXA4), known to promote inflammation resolution, may attenuate septic AKI via blocking crosstalk between inflammation and cellular senescence. In this study, rats developed AKI following cecal ligation and puncture (CLP), as evidenced by a dynamic increase in serum creatinine, blood urea n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…Emerging evidence indicates that senescence contributes to the progression of AKI and that senescence inhibition can promote kidney recovery. For example, inhibition of tubular cell senescence using lipoxin A4 restored renal function in a rat model of septic shock-induced AKI 173 . Similarly, in a rat model of contrast-induced AKI, pre-treatment with paricalcitol before contrast medium administration reduced cellular senescence (that is, expression of SABG and p16 INK4A ) and tissue damage and prevented kidney dysfunction 174 .…”
Section: Senescence In Kidney Diseasesmentioning
confidence: 99%
“…Emerging evidence indicates that senescence contributes to the progression of AKI and that senescence inhibition can promote kidney recovery. For example, inhibition of tubular cell senescence using lipoxin A4 restored renal function in a rat model of septic shock-induced AKI 173 . Similarly, in a rat model of contrast-induced AKI, pre-treatment with paricalcitol before contrast medium administration reduced cellular senescence (that is, expression of SABG and p16 INK4A ) and tissue damage and prevented kidney dysfunction 174 .…”
Section: Senescence In Kidney Diseasesmentioning
confidence: 99%
“…Recently, some novel mechanisms have been found involved in AKI. Chen et al found that crosstalk between connexin 32 and mitochondrial apoptotic signaling pathway plays a pivotal role in renal ischemia reperfusion-induced AKI and lipoxin A4 restores septic renal function via blocking crosstalk between inflammation and premature senescence [ 25 , 26 ]. Yuan et al reported that gap junction composed of Cx43 inhibition attenuated RIP1 and MLKL expression via mediating the content of ROS and then prevented acute kidney injury following liver transplantation [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…LXA4 pretreatment significantly restores kidney function and improves the survival rate of rats after cecal ligation and puncture (CLP). LXA4 inhibits NF-kappa B (NF/kB)–mediated inflammation and the p53/p21 senescence pathway in a PPAR-γ-dependent manner to alleviate kidney inflammation and renal TEC senescence [ 87 ]. Nicotinamide mononucleotide (NMN), when administered in advance or during the recovery phase, can reduce senescence and fibrosis in H 2 O 2 and hypoxia kidney injury, and ischemia–reperfusion-AKI mice [ 88 ].…”
Section: Senolytic Therapymentioning
confidence: 99%